High-density genetic mapping identifies the genetic basis of a natural colony morphology mutant in the root rot pathogen Armillaria ostoyae - Heinzelmann Renate (FUNGAL GENETICS AND BIOLOGY, 2017)
Abstract Filamentous fungi exhibit a broad spectrum of heritable growth patterns and morphological variations reflecting the adaptation of the different species to distinct ecological niches. But also within species, isolates show considerable variation in growth rates and other morphological characteristics. The genetic basis of this intraspecific variation in mycelial growth and morphology is currently poorly understood. By chance, a growth mutant in the root rot pathogen Armillaria ostoyae was discovered. The mutant phenotype was characterized by extremely compact and slow growth, as well as shorter aerial hyphae and hyphal compartments in comparison to the wildtype phenotype. Genetic analysis revealed that the abnormal phenotype is caused by a recessive mutation, which segregates as a single locus in sexual crosses. In order to identify the genetic basis of the mutant phenotype, we performed a quantitative trait locus (QTL) analysis. A mapping population of 198 haploid progeny was genotyped at 11’700 genome-wide single nucleotide polymorphisms (SNPs) making use of double digest restriction site associated DNA sequencing (ddRADseq). In accordance with the genetic analysis, a single significant QTL was identified for the abnormal growth phenotype. The QTL confidence interval spans a narrow, gene dense region of 87 kb in the A. ostoyae genome which contains 37 genes. Overall, our study reports the first high-density genetic map for an Armillaria species and shows its successful application in forward genetics by resolving the genetic basis of a mutant phenotype with a severe defect in hyphal growth.